CORRELATION BETWEEN DEPRESSION LEVEL AND LIFE QUALITY OF HIV PATIENTS AT POLY VCT REGIONAL GENERAL HOSPITAL PROF.DR. SOEKANDAR, MOJOKERTO - Imam Zainuri (Suluh Adiluhung Publisher (SAPub), 2024)
Life quality of HIV (Human Immunodeficiency Virus) patients is important to note because this infectious disease is chronic and progressive so that it has a wide impact on all aspects of life both physical, psychological, social, and spiritual. Psychosocial problems especially depression is more severe faced by patients so that it can reduce the life quality. The purpose of this study is to explain the relationship between depression and life quality in HIV patients. The design of this study used correlation analytic with non-probability sampling of consecutive types, conducted on June 23 until June 30, 2020, with 52 respondents. The research instrument used the WHO Life quality-BREF questionnaire to evaluate life quality and Beck Depression Inventory II to evaluate depression levels. The results of the study were tested with Spearman Rho and showed the level of depression in the non-depression category of (17.3%) 9 respondents in the mild category (13.5%) 7 respondents in the moderate category (32.7%) 17 respondents and in the severe category (36.5 %) 19 respondents and good life quality (42.3%) 22 respondents and poor category (57.7%) 30 respondents. From the results of the study obtained p value = (0,000) <α (0.05), which showed that there was correlation between depression level and life quality of HIV patients at Poly VCT Regional General Hospital Prof. Dr. Soekandar, Mojokerto. Depression contributed to a decrease in life quality of HIV patients, psychological burdens on sufferers such as sufferers felt pessimistic about the future, seeing themselves as worthless could have a dominant effect on decreasing life quality of HIV patients.